The function of local government autonomy in improving community-based security governance in Zamfara state: a secondary analysis - Arabo, U. A.; Gazali, S. (Journal of Social Review and Development, 2025)
In Zamfara State, Nigeria, banditry and kidnapping are making life very unsafe, which makes it challenging for the government to do its job well. This study looks at how providing local governments with greater autonomy could enable them to collaborate with communities to solve these security problems. The research investigates the challenges that Zamfara State's local governments confront, such as not having enough money and having to accept directives from the central government. It does this by using mostly existing data, such as government reports, academic studies, news stories and NGO publications, as well as a few targeted interviews with local officials. It also looks at successful local security measures in other Nigerian states, including community policing in Lagos, to see what Zamfara State may learn from them. The results suggest that local governments need more leeway to come up with solutions that work for their communities, such as local peace committees. The study advocates for reforms to empower local councils and build links between communities and government. By shedding light on an ignored sector of public administration, this work offers practical solutions for policymakers in Zamfara State and beyond, showing how local governance may make a difference in conflict zones.